The Resilience Function of Character Strengths in the Face of War and Protracted Conflict - Shoshani, Anat; Slone, Michelle (Frontiers in Psychology, 2016)
This study investigated the role of character strengths and virtues in moderating relations between conflict exposure and psychiatric symptoms among 1078 adolescents aged 13-15 living in southern Israel, who were exposed to lengthy periods of war and political violence. Adolescents were assessed for character strengths and virtues, political conflict exposure using the Political Life Events (PLE) scale, and psychiatric symptoms using the Brief Symptom Inventory and the UCLA PTSD Index. Results confirmed that political violence exposure was positively correlated with psychiatric symptoms. Interpersonal, temperance and transcendence strengths were negatively associated with psychiatric symptoms. Moderating effects of the interpersonal strengths on the relation between political violence exposure and the psychiatric and PTSD indices were confirmed. The findings extend existing knowledge about the resilience function of character strengths in exposure to protracted conflict and have important practical implications for applying strength-building practices for adolescents who grow up in war-affected environments.